Board Gender Diversity and Fraud in Indonesia’s Regional Banks: A Fraud Hexagon Perspective - Dwianto Mukhtar Latif; Widya Ais Sahla (Universitas Trunojoyo Madura, 2026)
This study investigates the determinants of financial reporting fraud using the Fraud Hexagon theory and examines the moderating role of women on the board of commissioners (WOC). This study employs a quantitative approach using Moderated Regression Analysis (MRA) with panel data from 27 Regional Development Banks during the period 2016–2023. The findings show that pressure, capability, opportunity, and arrogance significantly influence financial reporting fraud, while collusion is not significantly associated with fraud propensity. The results further indicate that the presence of women on the board of commissioners weakens the effect of pressure and capability on financial reporting fraud, highlighting their monitoring and governance-enhancing role. However, the effectiveness of WOC appears to be context-dependent, particularly influenced by the strength of corporate governance and internal control systems within banks. This study extends the empirical application of the Fraud Hexagon theory in explaining financial reporting fraud and provides evidence on the role of board gender diversity in fraud mitigation. By focusing on Indonesia’s Regional Development Banks—an underexplored sector—the findings offer practical implications for promoting ethical conduct and strengthening integrity-based corporate governance.